1997
DOI: 10.1002/(sici)1096-9861(19971208)389:1<94::aid-cne7>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of N-methyl-D-aspartate and non-N-methyl-D-aspartate glutamate receptor subunits on respiratory motor and premotor neurons in the rat

Abstract: Glutamate is required for the transmission of inspiratory drive in respiratory premotor and motor neurons. The glutamate receptors (GluRs) responsible for this essential function have yet to be anatomically characterized. We mapped the GluR subtypes expressed by respiratory premotor and motor neurons by using combined immunohistochemistry and retrograde labeling in adult rats. Phrenic motoneurons and bulbospinal ventral respiratory group (VRG) neurons were retrogradely labeled and immunolabeled with subunit-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 53 publications
3
20
0
Order By: Relevance
“…Glutamate NMDA and AMPA (α-amino-3-hydroxy-5-methyl-4-isoxazole propionate) receptors are present on phrenic motoneurons (Chitravanshi and Sapru, 1996; Dong and Feldman, 1999; Robinson and Ellenberger, 1997). A distinguishing feature of ionotropic NMDA receptors is that glutamate binding and post-synaptic depolarization activates the receptor and allows Ca 2+ to flow through the cell membrane along with the cations Na + and K + (Alpert and Alford).…”
Section: Role Of Bdnf/trkb and Glutamatergic Signaling In Phrenic mentioning
confidence: 99%
“…Glutamate NMDA and AMPA (α-amino-3-hydroxy-5-methyl-4-isoxazole propionate) receptors are present on phrenic motoneurons (Chitravanshi and Sapru, 1996; Dong and Feldman, 1999; Robinson and Ellenberger, 1997). A distinguishing feature of ionotropic NMDA receptors is that glutamate binding and post-synaptic depolarization activates the receptor and allows Ca 2+ to flow through the cell membrane along with the cations Na + and K + (Alpert and Alford).…”
Section: Role Of Bdnf/trkb and Glutamatergic Signaling In Phrenic mentioning
confidence: 99%
“…It is located in the rostroventrolateral medulla and relies on excitatory glutamatergic connections (Funk et al, 1993;Rekling and Feldman, 1998). PBC interneurons discharge through activation of NMDA and non-NMDA glutamate receptors (Funk et al, 1993(Funk et al, , 1997 and are immunopositive for glutamate receptor subunits (Robinson and Ellenberger, 1997;Paarmann et al, 2005). Neurokinin-1-receptor (NK1R)-expressing PBC neurons, essential for maintenance of normal breathing in vivo (Gray et al, 2001;McKay et al, 2005), have been shown to contain Vglut2 mRNA and to receive VGLUT2-positive terminals (Gray et al, 1999;Guyenet et al, 2002;Stornetta et al, 2003a,b) but also have GABAergic and glycinergic terminals (Liu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It follows that extracellular potassium (Rybak et al, 2003) and glutamate will control neuronal bursting by setting and modulating the membrane potential. Indeed, abundant expression of different ionotropic and metabotropic glutamate receptors has been described for the brainstem (Robinson and Ellenberger, 1997;Dong and Feldman, 1999).…”
Section: Introductionmentioning
confidence: 99%